Internal medicine evidence the practice-changing studies - Liao, Joshua M.; Kanjee, Zahir; Katz, Joel T.; Loscalzo, Joseph (Wolters Kluwer Health, 2017)
"In this volume, we aspired to select, summarize, and contextualize 100 of the most practice-changing articles in the field of Iinternal Mmedicine. As practicing clinicians, medical educators, and lifelong learners, we felt particularly drawn to the challenge of exploring how evidence guides clinical choices. In doing so, we hope to shed light on the strengths and weaknesses, clinical and historical context, and impacts and caveats of important research studies that underlie common and challenging clinical decisions"--Provided by publisher.